Do Elephants Have Knees? : And Other Stories of Darwinian Origins - Ault, Charles R., Jr., 1950- (Book collections on Project MUSE., 2017)
Thinking whimsically makes serious science accessible. That's a message that should be taken to heart by all readers who want to learn about evolution. This work invites readers into serious appreciation of Darwinian histories by deploying the playful thinking found in children's books. The text weds children's literature to recent research in paleontology and evolutionary biology. Inquiring into the origins of origins stories, the author presents three portraits of Charles Darwin - curious child, twentysomething adventurer, and elderly worm scientist.